POTENSI WISATA BUDAYA DI KAMPUNG BANDAR SEBAGAI IKON WISATA KOTA PEKANBARU - Meidya Riventi Hastanto; Sofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to determine the potential of cultural tourism in Kampung Bandar to serve as a Pekanbaru tourism icon according from travellers response who have visited Kampung Bandar.This research use deskriptif kuantitatif metode. There were 100 sampel of that people is taken by accidental sampling. The data collection techniques in this research used observation, interview, and questioners. The likert scale was used to measure the intervals in quantitative data.This research used Sukardi (1998 : 67). This theory divides the cultural potential to 4 category : Tradition, Handycraft, Art, and Historical Heritage.The result of this research shows that historical heritage of Mesjid Raya Pekanbaru is reasionable to be Pekanbaru tourism icon and other tourism potensial promotion need to improved for more people to know the tourism potential in Kampung Bandar is the origins of Pekanbaru city.Keyword : Potency, Culture Tour, Tradition, handycraft, Art, and Historical Heritage.